Teacher effectiveness: the beliefs of effective Bahasa Melayu teachers - Konting, Mohd Majid (Universiti Putra Malaysia Press, 1998)
Beliefs play a m~or role in the way teachers respond to an educational innovation such as the Integrated Curriculum for Secondary Schools (KBSM) in Malaysia. This paper gives an account of the effective teachers' perceptions of the notion of teacher effectiveness based on the teachers' theoretical understanding and their classroom practices. Twelve Bahasa Melayu teachers who were identified as effective in their teaching by the education authorities were studied through a semi-structured questionnaire which was later clarified through interviews. The results indicated that some of their beliefs are not parallel with those recommended and expected by the KBSM. This paper suggests that there is a need to consider teachers' beliefs in the planning and implementation of meaningful teacher education programmes.